Learning Heat Conductors and Insulators Using Video-Based Learning Media - Sari, Made Ratna Permata; Astawan, I Gede (International Journal of Elementary Education, 2021)
Less material exposure makes learning less effective, therefore innovations such as learning videos are needed, so that learning becomes interesting. The purpose of this study was to produce a demonstration-based learning video media on the topic of heat conductors and insulators in class V whose validity had been tested. This research is a development research (R&D). This study uses a 4D model consisting of four stages: define, design, development, and disseminate. The subjects of this research trial consisted of 2 material experts, 2 media experts, and 2 practitioners. The research data was collected by using a questionnaire method. The instrument used to measure the validity of the media is a rating scale with a scale of 4. The data were analyzed using the mean formula to determine the average media validity score. The results of the media validity in terms of material experts are 3.92, from media experts are 3.78, and in terms of practitioners are 3.78, with very good qualifications. So, the demonstration-based learning video media that was developed was declared valid. Democracy-based learning video media can be used as a solution in implementing innovative and interesting learning.